PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 33 TAMERAN KECAMATAN BENGKALIS - ', Nurdin; ', Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of  this Research is the weakness of student,s learning result of subject.It show from 22 student,s 8 students (36,36%) have lower score, and it is only 10 student,s ( 63,63%) have average score  59,27. the KKM of this school is 68. According to that problem,the Research by implementing learning model Quantum Learning . in cycle I, the percentage of teachers activity in First meeting is adquate 56,25 % . In second meeting ,teachers activity significantly increased to 65,62% with good category. In cycle II, first meeting was in good category 78,12% and second meeting indicated a very good category 90,62% Mean while, the activity of student,s also improved. In cycle I indicated 53,12% in adequate category and in cycle II has increased up to 62,50% with good category. In cycle II, First meeting, the activity of students has been increasing to 75,00% with good category and second meeting indicated very good category 87,50% . An average score of student,s learning result before implementation is 59,27. It increased to 66,50 in cycle I, and 70,00 in cycle II. In classical completeness, cycle I and cycle II Wet achieved. In conclussion, implementation learning model Quantum Learning can improve student,s learning result of fifth grade students of SDN 33 Tameran Kecamatan Bengkalis in social subject. Key words: Cooperative model Talking Stick,learning result of social subject